Episodic and declining fluvial processes in Noctis Fossae, Syria Planum Province, Mars. Issue 10 (15th November 2022) - Chavan, Anil; Sarkar, Subham; Bhandari, Subhash
Highlights: The valley network formation in the Noctis Fossae initiated in early Hesperian time. NNE-SSW trending grabens acted as the weak zone for water to flow. The episodic flow of water sustained for the entire Hesperian time. Fluvial activity declines in the Early Amazonian time. Abstract: The Noachian surfaces across Mars bear abundant evidence for aqueous processes; however, the transformation of the planet from warm and wet to the present-day cold and dry is unclear. A key question is whether these processes continued by the same or different magnitudes in the Hesperian and Amazonian times. The equatorial region of Mars has extensive sedimentary records of Hesperian time. The area includes Valles Marineris, Echus Plateau, Melas Basin, etc., with a probable water source from the glacial melt in the southern highland caused by heating due to Tharsis volcanism. The Noctis Fossae with extensive fluvial erosional channels situated on the transition zone between Valles Marineris and Tharsis has preserved evidence of flowing water. Our dataset includes mosaics of ∼6 m/pixel resolution Context Camera (CTX) images mapped in Arc-GIS software. The area has recorded NNE-SSW trending channels maintaining U-shaped glacial valleys at higher altitudes and V-shape fluvial valleys at lower altitudes forming parallel to subparallel drainage system, fluvial terraces, surfaces, and deep gorges on the Hesperian volcanic rocks. The progression of the faulting episodes centered at Syria Planum, Pavonis-I, and Pavonis-II has influenced the fluvial activity in the Noctis Fossae. The first phase of faulting centered at Syria Planum formed NNE-SSW trending grabens in the early Hesperian and created weak zones for the water to drain. The second phase of faulting centered at Pavonis-I induced the collapse of Noctis Labyrinthus in the south, concentrating water to the troughs, implying the decline in the fluvial processes in the early stages of Amazonian time. The third phase trending in the NW-SE direction cross-cuts all geomorphic units except younger scoria cones, which mark the most recent geological process in Noctis Fossae.